PENAMPILAN VEGETATIF DAN GENERATIF 10 GENOTIF GANDUM (Triticum aestivum L.) DENGAN VARIETAS KONTROL GURI-3 DI DATARAN MENENGAH, KELURAHAN BLOTONGAN, KECAMATAN SIDOREJO, KOTA SALATIGA, PROVINSI JAWA TENGAH - Pedro Jacob Bosco Amaral; Djoko Murdono (Universitas Muhammadiyah Purwokerto, 2018)
Research on vegetative and generative appearance of 10 wheat (Triticum aestivum L.) genotives was conducted in June 2017 until September 2017 in Blotongan Area, District Sidorejo, Salatiga which has a height of ± 698 m above sea level. The purpose of this study was to determine and obtain the appearance of vegetative and generative 10 genotypes of wheat that grow well in the plains medium. This research is using the RAK and analysis of variance with test HSD 5%. The treatments were 10 genotypes, namely: FUNDACEP 30, Filin / 2 * 1PASTAR 11 QUAIU, WBLL * 2KURUKU, PRL / 2 * PASTOR, Pfau / MILAN / 3 / SKAUZ / KS9, KIRITATI / 4/2 / * SERI.1B * 2, TRCH * 2/3 /C80.I/3, SAAR / 2 / * WAXWING, GURI 3. The treatment is repeated 3 times. The results showed that there is a difference in the appearance of vegetative between genotives tested in terms of plant height and number of leaves. While the number of tillers, flowering age, and harvest age is no different. On the appearance of the generative found no difference between genotives in terms of the number of seeds per panicle, seed weight per m2, the middle row 4th seed weight, seed weight per panicle, and the weight of 1000 seeds. While the length of spikelet number of panicle and seed weight of 1 liter is not unlike real; Genotif that has levels of appearance of vegetative and generative in the Middle Plains is PRL/2 * PASTOR and TRCH * 2/3/C80. I/3 relatively better than the varieties of Guri-3 as control varieties; Factors temperature, drought, soil pH, and soil texture when testing are causing high stress, so that the appearance of Guri-3 as control varieties haven't been able to emulate the appearance according to the description of the varieties of Guri-3.